Reframing The SIOP Model To Boost Teachers' Self Efficacy In Bilingual-Like Program: A Practical Concept Of An Alternative Model - Rozanah Katrina Herda; Angga Damayanto (Borneo Educational Journal (Borju), 2022)
The need to communicate through English and the desire to practice English in the teaching process has turned a public junior high school in Wonosobo, Indonesia, into one of the schools that hold an "English on Wednesdays" program to implement bilingual-like nuance. This conceptual paper highlights a natural phenomenon that occurs in that institution dealing with the desire to improve the competence of teachers and students in communication by programming "English on Wednesdays." The dilemmas related to teaching are felt by teachers, especially non-English teachers who do not have an English background, yet they are enthusiastic about this program. Thus, this paper will propose a framework called "The Alternative SIOP Model" that will help teachers overcome the dilemmas in teaching the "English on Wednesdays" program that emphasizes self-efficacy to develop teachers' competencies on lesson preparation and communication. This conceptual paper used the systemic review to gain information from theories and research findings related to the topic. Keywords: teachers' dilemmas; teachers' self-efficacy; the alternative SIOP Model